Current Globalization: A Challenge For The Humanities - Yanitsky, Oleg (Advances in Social Sciences Research Journal, 2017)
Globalization and the New Technological revolution as its driving force challenge the humanities. The growing unfitness between a highly complex and risky globalization process and current sort-term and monodisciplinary approach to the study of it is characteristic to the majority of the humanities. To my mind, new object of study, the sociobiotechnical systems (hereafter, the SBT-systems) have emerged in which social, biological and technical structures and processes are highly integrated by various metabolic processes. Therefore, dichotomy approaches like ‘man—nature’, ‘rural—urban’, ‘we—they’, ‘here—there’ are not fit to integrative character of globalization processes. This gap should be overcome by problem-oriented and interdisciplinary researches taking into account a global-local and multidisciplinary character of ongoing transformations. A view of an insider from any ‘focal point’ of globalization is as important as the study carried out by an outer observer. The recent development of humanitarian studies and its institutional structure should ‘follow the actor’ principle, be such actor a rank-and-file, a politician or a state. A ‘humanities—technological innovation—social life’ interactions should be studied at all levels of the SBT-system functioning and evolution. All in all, the humanities should be gradually modernized.